ANATOMY OF THE JUGULAR FORAMEN IN DRY HUMAN SKULLS OF DIFFERENT GENDERS - Rzayeva, A.M. (World of Medicine and Biology, 2025)
The purpose of the study was to examine certain morphometric parameters of the jugular foramen in dry adult human skulls classified by gender. The study was conducted on 77 “documented” dry skulls (38 male, 39 female), retrieved from the bone collection of the Anatomical Museum at the Department of Human Anatomy and Medical Terminology. Differences between the two groups were assessed using the non-parametric Mann–Whitney U test (PU). Descriptive t-test and Dispersion F-test (ANOVA) were also applied. A statistical significance of p